Yearbook on Space Policy 2010/2011 The Forward Look - Hulsroj, Peter; Pagkratis, Spyros; Baranes, Blandina; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
The Yearbook on Space Policy is the reference publication analysing space policy developments. Each year it presents issues and trends in space policy and the space sector as a whole. Its scope is global and its perspective is European. The Yearbook also links space policy with other policy areas. It highlights specific events and issues, and provides useful insights, data and information on space activities. The Yearbook on Space Policy is edited by the European Space Policy Institute (ESPI) based in Vienna, Austria. It combines in-house research and contributions of members of the European Space Policy Research and Academic Network (ESPRAN), coordinated by ESPI. The Yearbook is designed for government decision-makers and agencies, industry professionals, as well as the service sectors, researchers and scientists and the interested public.
Space-based capabilities for internal security operations: a critical assessment of the case of land-border-surveillance -- European access to space: challenges and perspectives -- What future for GEOSS? Results from the November 2010 GEO Ministerial Meeting -- The new German Space Strategy: how strategic is it? -- Cooperation in space between Europe and Israel in light of the recent ESA-ISA agreement -- Recent development of Japan's space policy: the Quasi-zenith satellite program and the space policy making process -- Space debris - legal framework, issues arising and new ISO guidelines in 2010/2011 -- Digital devide and the global crisis -- Towards a space strategy for the EU that benefits its citizens: the EU's declaration of intents for space -- The establishment of the US space agency.
Keywords: Engineering; Astronautics; Economics; Engineering; Aerospace Technology and Astronautics; Political Science, general; Law of the Sea, Air and Outer Space; R & D/Technology Policy